Pharmacokinetic Compatibility Study of Lidocaine with EXPAREL in Yucatan Miniature Pigs. (10th October 2011) - Richard, Brigitte M.; Rickert, Douglas E.; Doolittle, Dannette; Mize, Amy; Liu, Jason; Lawson, Charles F.
Abstract : We explored the potential for EXPAREL to interact with lidocaine. Sixty (60) male Yucatan Swine were randomized into 20 groups (N = 3 /group). EXPAREL (2 or 4 mg/kg) and/or lidocaine HCl solution 1% or 2% (with epinephrine 1 : 200, 000) were injected subcutaneously along a 5 cm virtual incision line. The effects on the pharmacokinetics of bupivacaine and lidocaine were examined when 5, 10, 20, and 40 minutes had passed between administration of lidocaine and EXPAREL. Systemic exposure to lidocaine was increased (AUC 0 − 24  hr by 48%;C max by 1, 640%) when lidocaine (4 mg/kg) was followed 5 minutes later by EXPAREL (4 mg/kg) compared to lidocaine administered alone. Plasma bupivacaine was increased (AUC 0 − 24  hr by 50–95%;C max by 67–1, 000%) when lidocaine (4 mg/kg) was followed 5 or 10 minutes later by EXPAREL (4 mg/kg) compared to EXPAREL alone. While EXPAREL should not be admixed with lidocaine, this study shows that local administration of EXPAREL after at least 20 minutes following local administration of lidocaine did not increase the release of either drug.